Simulation evaluation of DiffServ approach integrated in MIPv6 networks - Hussien, Loay F.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Khalifa, Othman Omran; Hameed, Shihab A.; Al-Khateeb, Wajdi Fawzi Mohammed (INSI Publications, 2011)
Nowadays the Best-Effort (BE) service that is provided by the Internet is not good enough. Namely, it is adequate only for traditional Internet applications such as e-mail, web browsing and file transfer. However, recently we have seen a hug revolution in real-time applications like IP-telephony, multimedia conferencing, e-commerce, audio and video streaming. These types of applications require resource assurance and service differentiation to offer QoS guarantees (i.e. high bandwidth, low delay and/or delay variation). Working on providing QoS in the Internet has led to three distinct approaches endorsed by Internet Engineering Task Force (IETF) namely, IntServ, DiffServ and MPLS. Above all, the most promising one due to its simplicity and scalability advantages is Differentiated Service (DiffServ). The DiffServ approach was initially designed without mobility in-mind. It is still not fully adapted to mobile environments yet. Obviously, integrating QoS with mobility support seems to be needed to fulfill the necessity of users. Therefore, one of main requirements of next generation IP based networks is providing QoS for real-time traffic that will be transporting through MIPv6 networks. This paper aims to propose a new scheme that takes the advantage of DiffServ to enhance QoS in the mobile IPv6 network. The proposed scheme was evaluated by using NS-2. The proposed scheme is benchmarked with the standard MIPv6 which was proposed by IETF. The obtained results show that the proposed scheme outperforms the standard MIPv6 protocol in terms of packets loss and handover latency.